Assessing academic entitlement in pharmacy students: insights from Saudi Arabia - Dalia Almaghaslah; Bayan Alamri (Frontiers in Medicine)
BackgroundAcademic entitlement, characterized by students’ expectations of academic rewards without proportional effort, has become an emerging concern in higher education, particularly in pharmacy programs. Understanding the demographic factors contributing to this phenomenon can help institutions design targeted interventions to mitigate its effects.AimThe aim of this study was to assess Academic Entitlement (AE) its seven subscales, including Rewards for Effort, Accommodation, Responsibility Avoidance, Customer Orientation, Customer Service Expectation, and Grade Haggling among pharmacy students in Saudi Arabia. Also to assess association between AE and demographics including age, gender and GPA.MethodsA 17-item Academic Entitlement Questionnaire was distributed to pharmacy students through an online survey. The questionnaire, translated into Arabic using the back-translation method, was piloted for clarity before distribution. Data were analyzed using inferential statistics to assess the association between academic entitlement and key demographic variables.ResultsA total of 267 pharmacy students enrolled in Pharm D program participated in the study. Statistical analysis revealed significant associations between academic entitlement and specific demographic factors: Age: A significant relationship was observed (P = 0.032), indicating variations in entitlement levels across age groups. Gender: No significant relationship was found (P = 0.242). GPA: No significant association was identified (P = 0.42), suggesting entitlement levels may vary with academic performance. These findings suggest that younger students may exhibit higher levels of academic entitlement.ConclusionAcademic entitlement among pharmacy students is influenced by demographic factors, with significant associations observed for age. These findings highlight the need for educational strategies that address entitlement behaviors, particularly among younger, to maintain academic rigor and professional accountability. Further research is needed to explore underlying causes and effective interventions.